Kansas State SEE green campaign: Live green, bleed purple - Spexarth, Rebecca; Besler, Erica (Kansas State University, 2009)
SEE Green is a year long student-driven campaign to developed by the Student Director of Sustainability in conjunction with the Student Sustainability Coalition. The K-State Director of Sustainability serves as the faculty advisor of the SSC and oversees the progress of the SEE Green Campaign. The purpose of the SEE Green Campaign is to educate and empower K-State students to improve sustainability at K-State and in their community. There are three topics that the SEE Green is focusing on: transportation, recycling, and energy usage.
Keywords: Kansas State University; Transportation; Recycling; Energy Use